REVISION OF THE INDO-PACIFIC SPHENOCARCINUS WITH A SINGLE ROSTRUM AND DESCRIPTION OF TWO NEW SPECIES (CRUSTACEA, DECAPODA, BRACHYURA, MAJIDAE) - Guinot, D.; De Forges, B. Richer (Marine Research in Indonesia, 1984)
Two species of the genus Sphenocarcinus A. Milne Edwards 1876, with a single rostrum exist in the Indo-Pacific and they are principally only known by their original description: S. cuneus (Wood-Mason 1891) and S. aurorae Alcock 1899. Each species is herewith redescribed, based on the examination of the types. Two new species are established. S. difficilis sp. nov., represented by numerous specimens from Madagascar (ORSTOM collection), proved to be an intermediate species between S. cuneus and S. aurorae. S. pinocchio sp. nov., (collected in the Makassar Strait, Indonesia (mission Corindon II), is characterized by its very Jong and strongly curved rostrum. One male specimen, also collected in the Makassar Strait, probably modified by a sacculinid parasite, and with a more curved, snub rostrum, can be regarded as an unusual form of S. pinocchio sp. nov. A key of the four Indo-Pacific Sphenocarcinus with a single rostrum is presented.